Active alignment control system for thin disk regenerative amplifier - Horáček, J; Hubka, L; Chyla, M; Mocek, T (The Review of scientific instruments, 2025)
We present an active alignment and stabilization control system for laser setups based on a thin-disk regenerative amplifier. This method eliminates power and pointing instability during the warm-up period and improves long-term stability throughout the entire operation. The alignment method is based on a four-mirror control system consisting of two motorized mirrors placed within the regenerative amplifier cavity, two additional motorized mirrors external to the amplifier cavity, and four camera detectors. The implemented stabilization system achieves significant performance improvements, increasing the power stability from 1.87% to 0.79% RMS and the peak-to-peak stability from 7.43% to 3.88%. Furthermore, the system significantly enhances beam positional stability, achieving up to a sixfold improvement in certain sensor measurements. The advantage of this method is the removal of long-term pointing instability by adding a second controlled motorized mirror to the cavity, in addition to using only one cavity end mirror for optimizing the overlap with the pump spot on the cavity medium. To achieve higher precision in pointing, the nonlinear hysteresis effect of the piezoelectric actuator is mitigated. Although the power and pointing stability of the cavity are secured, pointing instability at the input of the compressor occurs. This issue is resolved by two additional controlled motorized mirrors external to the cavity.